Duodenal Peptic Ulcer Perforation in the Puerperium Case Report Series - Elizabeth Stiles; Andre Robinson; Erin Fitzgerald; Marie Fleury; Andrew Rubenstein (American Journal of Perinatology Reports)
Peptic ulcers, and complications such as perforation, are rare during pregnancy and the puerperium. Accordingly, many clinicians may place these diagnoses low on their differential diagnosis. We present two case reports of primigravida, advanced maternal age females with history of irritable bowel syndrome and nonsteroidal anti-inflammatory drug (NSAID) use found to have perforated duodenal ulcers after Cesarean section. Postpartum surgical abdomens may not present with classic guarding and rigidity. A low threshold for imaging and identification of risk factors are critical to timely diagnosis and management.